Demo abstract: ViSiM, A MANET routing simulation demonstration tool for naive users - Saquib, Nazmus; Sakib, Md. Sabbir Rahman; Pathan, Al-Sakib Khan (2010)
The task of simulation is often complicated for which many naive users often seek for relatively easier solutions. In many cases, simulations are done without any visual output which makes them non-attractive. In this demo, we present ViSim; a new simulation demonstration tool that has a user-friendly graphical interface. ViSim could be useful for researchers, students, teachers in their works, and for the demonstration of various wireless network scenarios on the computer screen. It could make the task of simulation more exciting and enhance the interest of the users without going into complex command-only text interface. For naive users, it is a demonstration tool; for experts, it could be used for performing various types of simulations in ns-2 using Windows environment.